2011
DOI: 10.4103/2229-5119.86258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral administration of ethanolic root extract of Tinospora cordifolia on aflatoxin B1-induced toxicity in swiss albino mice

Abstract: Background: Afl atoxins are potent hepatotoxic and hepatocarcinogenic agents. This hepatotoxicity is thought to be mediated by their ability to generate reactive oxygen species and cause peroxidative damage. Considering the antioxidant properties of Tinospora cordifolia, this study was undertaken to evaluate the therapeutic effi cacy of Tinospora cordifolia root extract in terms of altered biochemical, hematological, serological and histopathological parameters. Methods: Sixty male swiss albino mice were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Non-significant effect on CAT and SOD activity was observed on treatment with Withania somnifera root extract as compared to untreated animals [14] supported the present study. However, a significant increase in the plasma CAT and SOD activity was observed by Das et al [15] and El-Sabbagh et al [16] reporting that the herb possesses antioxidant properties, and administration of an aqueous root extract of Withania somnifera for 25 days increased the values of CAT and SOD in dehydration-induced oxidative stress-related uremia in male rats.…”
Section: Resultssupporting
confidence: 88%
“…Non-significant effect on CAT and SOD activity was observed on treatment with Withania somnifera root extract as compared to untreated animals [14] supported the present study. However, a significant increase in the plasma CAT and SOD activity was observed by Das et al [15] and El-Sabbagh et al [16] reporting that the herb possesses antioxidant properties, and administration of an aqueous root extract of Withania somnifera for 25 days increased the values of CAT and SOD in dehydration-induced oxidative stress-related uremia in male rats.…”
Section: Resultssupporting
confidence: 88%
“…found to significantly reduce the increased activities of serum marker enzymes AST, ALT, ALP and total bilirubin level. Our study reveals comparative hepatoprotective effect T. cordifolia, T. sinensis and Neem-guduchi Satwa which is similar to the previous studies done to explore the hepatoprotective effect of T. cordifolia alone [40][41][42][43][44][45]. However, there is no report so far on possible hepatoprotective mechanism of aqueous stem extract of both species.…”
Section: Discussionsupporting
confidence: 87%
“…This could be due to the capability of lophirones B and C to enhance the expression of Nrf‐2 . Brahmi et al and Sharma et al reported similar protection against the AFB 1 ‐mediated decrease in antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 88%
“…This could be due to the capability of lophirones B and C to enhance the expression of Nrf-2 [14]. Brahmi et al [33] and Sharma et al [34] reported similar protection against the AFB 1mediated decrease in antioxidant enzymes. AFB 1 -mediated reduction in the levels of GSH, GSH-Px cofactor, might have resulted from the depleted GSH-Px and GSH-Red activities [35].…”
Section: Discussionmentioning
confidence: 89%